2000
DOI: 10.1054/bjoc.2000.1501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of genomic alterations in minimal residual cancer cells purified from the blood of breast cancer patients

Abstract: SummaryThe prognostic value of disseminated tumour cells derived from 353 breast cancer patients was evaluated. Disseminated tumour cells were purified from blood using a newly established method and nucleic acids were subsequently isolated. We investigated genomic imbalances (GI) such as mutation, amplification and loss of heterozygosity of 13 tumour suppressor genes and 2 proto-oncogenes using DNA from isolated minimal residual cancer cells. Significant correlations were found between genomic alterations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Cancer cell fractions were isolated from 7.5 mL blood, and molecular analysis was carried out in two populations of circulating disease cells, namely EPCAM + CECs and CCCs. Both classes of circulating tumour cells have been enriched from mononucleated cells (MNCs) as described recently [ 4,7,8 ] . As published by our laboratory in 2000 [ 8 ] , spiking experiments in blood with aggregates or individual, dispersed EPCAM + epithelial cells from SW480 cultures have shown that the two cell types to be isolated represent two different classes of circulating disease cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer cell fractions were isolated from 7.5 mL blood, and molecular analysis was carried out in two populations of circulating disease cells, namely EPCAM + CECs and CCCs. Both classes of circulating tumour cells have been enriched from mononucleated cells (MNCs) as described recently [ 4,7,8 ] . As published by our laboratory in 2000 [ 8 ] , spiking experiments in blood with aggregates or individual, dispersed EPCAM + epithelial cells from SW480 cultures have shown that the two cell types to be isolated represent two different classes of circulating disease cells.…”
Section: Methodsmentioning
confidence: 99%
“…2 ). The methods were published by our laboratory in detail in 2000 [ 8 ] . Briefl y, clusters were captured in the fi ltrate matrix whereas individual cells would pass through the matrix and appear in the fi ltrate; therefore, scattered non-aggregated SW 480 cells were applied to determine their presence in CCCs ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a better understanding CTC biology is likely to reveal previously unavailable information about the mechanisms of metastasis. For example, genetic changes can be detected in CTCs, including abnormal telomerase activity (Soria et al, 1999), allelic loss and/or amplification of multiple oncogenes not seen in normal control populations (Austrup et al, 2000), and aneuploid changes in cellular chromosome content based upon FISH analysis similar to those seen in the primary tumour (Fehm et al, 2002). Additionally, cancer-associated protein expression by CTCs can be detected, such as HER2 (Figure 2) (Hayes et al, 2002).…”
Section: Future Directionsmentioning
confidence: 99%
“…the detection of circulating tumor cells (ctcs) in the peripheral blood of patients with different neoplastic diseases has been used as an early potential marker of the metastatic spread of malignant cells in the bloodstream (2)(3)(4)(5)(6), and is, therefore, considered a sign of poor prognosis (7)(8)(9)(10)(11). In fact, the malignant nature of ctcs has been established in previous studies by the identification of tumor-specific chromosomal aberrations (2) and other genetic changes (12,13), as well as by their in vitro growth with cancer cell-like behaviour (14). In addition, in several studies the number of ctcs detected seems to correlate with the aggressiveness of different advanced malignancies, such as breast (9,15,16), prostate (17,18) and colorectal cancer (19).…”
Section: Introductionmentioning
confidence: 99%